A review on Cold Storage Monitoring system and Data Analysis (International Journal of Food and Nutritional Sciences, 2022)
Cold storage is a warehouse where all the essentials are being stored like agricultural products, medicines, pharmaceutical products, chemicals, Food products like frozen food, seafood, and food grain in order to preserve and prevent loss. Cold Storage is a developing sector all around the globe. Which needs a maximum development in order to preserve the products for a longer duration. For maintaining those products for a long duration these need to be well preserved to avoid spoilage of those items. A constant temperature, humidity, light intensity etc. needs to be maintained inside the storage unit. But here comes the major issue without human intervention it is not possible to maintain the temperature constant manually, with the help of IoT monitoring systems those temperatures can be monitored without any human intervention. The data collected by the sensors present will be stored in the cloud. Artificial intelligence methods like Machine learning and Deep learning algorithms made analyzing of data easy.